Social capital as the basis of intersectoral social partnership - PLOTNIKOV, ALEXEY IVANOVICH (The journal of contemporary issues in business and government, 2021)
This article considers social capital as the basis for intersectoral social partnership based on the interpretation of the essence of social capital, indentifyning its main features: non-monetary nature, trust, ability to self-growth with increasing frequency of use, allowing successful solving of social problems. Particular attention is paid to trust as the foundation of the organization of social interaction and an indicator of the size of social capital. As a result of comparing the concepts of social capital and intersectoral social partnership, the author identifies a key feature characterizing social capital and intersectoral social partnership – interaction with the goal of development, which in turn allows us to consider social capital and intersectoral social partnership as intercomplementary processes. Based on the consideration of the main features of social capital, its structure and essence as a process, the author concludes that social capital is the basis of intersectoral social partnership, its integral part and necessary basis for the development of civil society and the formation of a social state.